Survival of Patients with Malignant Pleural Effusion: A Single Center Study - Mohammad Javad Fallahi; Alireza Rezvani; Zainab Al-Saif (مجله علوم پزشکی صدرا)
Malignant pleural effusion is one of the most common complications of advanced malignancies, leading to decreased quality of life and life expectancy. With the advent of new therapies, patients with malignant pleural effusion appear to be living longer than previously thought. In this cohort study,26 patients, with malignant pleural effusion at the initial diagnosis of primary cancer, who were referred to the Lung Cancer Clinic of Shahid Motahari Clinic affiliated with Shiraz University of Medical Sciences , were studied Information on age, sex, tumor type, mortality, survival rate after malignant pleural effusion, EGFR mutation (in lung cancer patients), and metastasis were evaluated. In the present study, 12 patients (46.2%) were male and 14 patients (53.8%) were female. The median survival of patients was 2 years (interquartile range 1-3 years). Five patients (19.2%) had breast cancer, 19 patients (77.1%) had lung cancer, and two patients (7.7%) had lymphoma. The highest survival after diagnosis was related to one of the lymphoma patients (five years). In lung and breast cancer patients, the median survival was two years (interquartile range 1.5, 3) and one year (interquartile range 1, 2.5), respectively. Although the present study was a small single-center study, due to the appropriate lifespan of malignant pleural effusion patients with new therapies, more comprehensive studies are needed to re-evaluate the survival of patients with malignant pleural effusion.